Across the wide Missouri - DeVoto, Bernard Augustine, 1897-1955 (Houghton Mifflin, 1947)
Winner of the Pulitzer Prize and the Bancroft Prize. Across the Wide Missouri tells the compelling story of the climax and decline of the Rocky Mountain fur trade during the 1830s. More than a history, it portrays the mountain fur trade as a way of business and a way of life, vividly illustrating how it shaped the expansion of the American West.